A Semantics for Weak, Question-Sensitive Belief - Jovićević, Andrej (Proceedings of the Amsterdam Colloquium, 2024)
Recent work in epistemology defends the unorthodox theses that belief is (1) an evidentially weak, and (2) question-sensitive attitude, and (3) that forming beliefs is sometimes a matter of guessing. What motivates these theses are examples of rationally permissible belief-ascriptions that exhibit these traits. The main aim of this paper is to outline a semantic account of categorical and conditional belief-ascriptions that captures the motivating data. We then survey some consequences of the proposed semantics, particularly with respect to the question of whether closure under rules of inference is rationally required for weak, question-sensitive belief.